Study on the Impact of Digital Inclusive Finance on Urban and Rural Residents' Entrepreneurship - Lu, Yanna (International Journal of Global Economics and Management, 2024)
Based on the number of newly registered enterprises each year as a measure of the level of entrepreneurship among urban and rural residents, this study empirically examines the impact of digital inclusive finance on entrepreneurial activities based on panel data from 31 provinces across the country and digital inclusive finance indices from 2011 to 2020. The findings reveal that digital inclusive finance significantly promotes entrepreneurial activities overall. In terms of specific indicators, this promotion effect is primarily driven by the dimensions of coverage breadth and usage depth. When dividing the total sample into four regions: East, Central, West, and Northeast, the study further explores the impact of digital inclusive finance on entrepreneurial behavior in urban and rural areas and across different regions. Therefore, it is recommended to accelerate the development and construction of digital inclusive finance, strengthen the establishment of comprehensive digital infrastructure, and promote the deep integration of digital inclusive finance with traditional industries. This will optimize the allocation of financial resources while also achieving industrial structure optimization and upgrading.